Effect of Scapular Stabilization in Improving Shoulder Range of Motion and Reducing Pain Among Patients with Upper Crossed Syndrome - Kshtrashal Singh; Yu Chye Wah; Rishikesavan.R; Pavithra Annamalai (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: Upper Crossed Syndrome is a common musculoskeletal condition characterized by muscle imbalances around the neck and shoulders, leading to poor posture and reduced shoulder range of motion (ROM). This study explores the effectiveness of scapular stabilization exercises in improving shoulder ROM and reducing pain in Upper Crossed Syndrome patients. Aim: To evaluate the impact of scapular stabilization exercises on shoulder ROM and pain reduction in individuals with Upper Crossed Syndrome compared to conventional physiotherapy methods. Methods: A randomized controlled trial was conducted with 61 participants diagnosed with Upper Crossed Syndrome, divided into a control group (n=30) receiving conventional physiotherapy and an experimental group (n=31) receiving scapular stabilization exercises. The interventions were performed three times a week for eight weeks. Pain was assessed using the Visual Analogue Scale (VAS), and shoulder ROM was measured using goniometry. Results: Post-intervention, the experimental group showed a significant reduction in VAS scores (mean reduction of 2.84) and improvement in shoulder ROM across all movements, including flexion, extension, and internal rotation. The control group also demonstrated improvements, but the changes were less pronounced compared to the experimental group. Discussion: The findings suggest that incorporating scapular stabilization exercises in Upper Crossed Syndrome rehabilitation leads to better outcomes in pain relief and shoulder mobility. The superior results in the experimental group highlight the importance of addressing scapular mechanics for optimal shoulder function. Conclusion: Scapular stabilization exercises are more effective than conventional physiotherapy in managing Upper Crossed Syndrome, offering significant benefits in pain reduction and improving shoulder ROM. This approach should be considered for inclusion in standard Upper Crossed Syndrome rehabilitation protocols. Further research with larger sample sizes and extended follow-up periods is recommended to validate these findings.